Determinants of functional diagnosis and strategies of work in school relations with students with diverse educational needs - Marta Ewa Niemiec (Edukacyjna Analiza Transakcyjna)
Currently, functional diagnosis is becoming an essential part of teaching and learning processes at school. It allows for the identification of students’ needs and the adaptation of teaching strategies to the individual skills and abilities of each student. To properly perform a functional diagnosis, it is necessary to consider many conditions. This paper focuses on the analysis of the most current concepts concerning the essence, assumptions, characteristics and principles related to the functional diagnostic process, which are the result of many years of theoretical, practical and scientific work of a large group of specialists investigating this issue. The paper also presents a fragment of the author’s research on the perception of functional diagnosis and its determinants in the current educational reality by active teachers and students of special education. A qualitative strategy was used. The method of a semi-structured, individual written interview was applied. This study also contains conclusions from the research, observations and implications for pedagogical practice regarding factors that may foster better effectiveness of the diagnostic process and the strategies applied in educational and therapeutic work with students with diverse needs in institutions available to general public.